Clojure high performance programming : understand performance aspects and write high performance code with Clojure - Kumar, Shantanu (Community experience distilled., 2013)
This is a short, practical guide that will teach you everything you need to know to start writing high performance Clojure code. This book is ideal for intermediate Clojure developers who are looking to get a good grip on how to achieve optimum performance. You should already have some experience with Clojure and it would help if you already know a little bit of Java. Knowledge of performance analysis and engineering is not required. For hands-on practice, you should have access to Clojure REPL with Leiningen.